2009
DOI: 10.1111/j.1471-6712.2008.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived health status as measured by the SF‐36 in patients with multiple sclerosis: a review

Abstract: This review of literature gives an overview of recent studies about perceived health status as measured by the Short-Form-36 (SF-36) Health Survey in patients with multiple sclerosis (MS). The SF-36 is one of the tools measuring health status in patients used in international research and clinical practice. It measures two main health concepts - physical and mental. The SF-36 represents a valid instrument able to detect differences in perceived health status in patients. A computer-aided search in Medline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 39 publications
5
35
0
Order By: Relevance
“…Gender issues in multiple sclerosis -Review questionnaire (eight studies), and acknowledged similar results for men and women [299]; this is concordant with others studies [300][301][302][303][304][305][306]. A few studies report that women [298,[307][308][309] or men [310][311][312][313] have a better QoL.…”
Section: Self-assessment Of Health and Qolsupporting
confidence: 82%
“…Gender issues in multiple sclerosis -Review questionnaire (eight studies), and acknowledged similar results for men and women [299]; this is concordant with others studies [300][301][302][303][304][305][306]. A few studies report that women [298,[307][308][309] or men [310][311][312][313] have a better QoL.…”
Section: Self-assessment Of Health and Qolsupporting
confidence: 82%
“…Self-reported measures of behaviourspecific self-efficacy (5 items each) [16,70] -Manage your disease -Managing your symptoms Subjective health status SF-36 V2 [54] Self-reported measure of health status (36-items) [71,72] Health related quality of life WHOQOL-BREF measure [55] (New Zealand version [73])…”
Section: Feasibility and Acceptability Of The Interventionmentioning
confidence: 99%
“…Previous research has suggested that social support is related to adaptation to MS disability, the quality of life related to health (HRQoL), psychological well-being and survival of people with chronic diseases [1][2][3][4][5][6][7][8][9][10][11][12][13] . The concept of social support has polysemic characteristics; however, there is a broad consensus about its different meanings based on a set of conceptual dimensions which supports empirical investigation 11 .…”
mentioning
confidence: 99%
“…Previous research has shown that it is connected to actions of family and social reciprocity, has a positive effect on the overall health of patients 16 and on the life of caregivers 17,18 , reducing its burden [19][20][21] . High levels of social support are also associated with high levels of HRQoL and low levels of depression among patients with MS 4,6,8,22 . The research also highlights the predictive value of social support on the physical and mental dimension of HRQoL 4,6,8,9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation